A search for cyanopolyynes in L1157-B1. Issue 4 (23rd January 2018) - Mendoza, Edgar; Lefloch, B; Ceccarelli, C; Kahane, C; Jaber, A A; Podio, L; Benedettini, M; Codella, C; Viti, S; Jimenez-Serra, I; Lepine, J R D; Boechat-Roberty, H M; et al.
Abstract: We present here a systematic search for cyanopolyynes in the shock region L1157-B1 and its associated protostar L1157-mm in the framework of the Large Program'Astrochemical Surveys At IRAM' (ASAI), dedicated to chemical surveys of solar-type star-forming regions with the IRAM 30-m telescope. Observations of the millimeter windows between 72 and 272 GHz permitted the detection of HC3 N and its 13C isotopologues, and HC5 N (for the first time in a protostellar shock region). In the shock, the analysis of the line profiles shows that the emission arises from the outflow cavities associated with L1157-B1 and L1157-B2. Molecular abundances and excitation conditions were obtained from the analysis of the Spectral Line Energy Distributions under the assumption of Local Thermodynamical Equilibrium or using a radiative transfer code in the Large Velocity Gradient approximation. Towards L1157 mm, the HC3 N emission arises from the cold envelope (T_rot=10K ) and a higher-excitation region ( T rot = 31K ) of smaller extent around the protostar. We did not find any evidence of 13 C or D fractionation enrichment towards L1157-B1. We obtain a relative abundance ratio HC3 N/HC5 N of 3.3 in the shocked gas. We find an increase by a factor of 30 of the HC3 N abundance between the envelope of L1157-mm and the shock region itself. Altogether, these results are consistent with a scenario in which the bulk of HC3 N was produced by means of gas phase reactions in the passage of the shock. This scenario is supported by the predictions of a parametric shock code coupled with the chemical model UCL_CHEM.